2012
DOI: 10.3348/kjr.2012.13.3.283
|View full text |Cite
|
Sign up to set email alerts
|

Value of CT in the Discrimination of Fatal from Non-Fatal Stercoral Colitis

Abstract: ObjectiveClinical presentation and physical signs may be unreliable in the diagnosis of stercoral colitis (SC). This study evaluates the value of computed tomography (CT) in distinguishing fatal from non-fatal SC.Materials and MethodsTen patients diagnosed as SC were obtained from inter-specialist conferences. Additional 13 patients with suspected SC were identified via the Radiology Information System (RIS). These patients were divided into two groups; fatal and non-fatal SCs. Their CT images are reviewed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 27 publications
0
54
0
Order By: Relevance
“…In a recently published article, Wu et al (3) reported that dense mucosa sign had a significant correlation with fatal SC. They evaluated dense mucosa sign in unenhanced CT images and concluded that mucosal sloughing sign and pericolonic abscess have high specificity (100% and 93%, respectively) for the diagnosis of fatal SC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recently published article, Wu et al (3) reported that dense mucosa sign had a significant correlation with fatal SC. They evaluated dense mucosa sign in unenhanced CT images and concluded that mucosal sloughing sign and pericolonic abscess have high specificity (100% and 93%, respectively) for the diagnosis of fatal SC.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, presence of free fluid or abscess indicates a more complicated incident, since presence of fluid may suggest associated infection with or without accompanying leakage from the colon. Wu et al (3) reported that the incidence of CT signs of dense mucosa, perfusion defect, free fluid, and abnormal gas was statistically different between fatal and nonfatal SC. In addition to these CT features, we found affected colon segment length >40 cm to be associated with increased mortality in SC.…”
Section: Discussionmentioning
confidence: 99%
“…CT of the abdomen expedites diagnosis and treatment of stercoral colitis. CT findings of stercoral colitis include fecal impaction, pericolonic fat stranding, colon wall thickening > 3 mm, and proximal colonic dilatation [4,13]. In our patient's tomography, wall thickness was over 3 mm in the rectosigmoid region.…”
Section: Discussionmentioning
confidence: 55%
“…In stercoral colitis without perforation, 52% of patients can be treated non-operatively with a bowel regimen. The remainder deteriorates clinically and ultimately require surgery [13]. Methods to extract feces from the rectum, including digital disimpaction and enemas, do not improve abdominal discomfort [4].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple objective scales have been studied to quantify fecal loading on abdominal radiographs, mostly in pediatrics, and none are reliable. [73][74][75][76][77][78][79] Stercoral colitis is often not suspected before imaging and first suggested on CT. 80 There is no publication describing the MR imaging or ultrasound appearance of stercoral colitis.…”
Section: Imaging Methods and Techniquesmentioning
confidence: 97%